Analysis of formaldehyde content in salted fish at Ciroyom market, Bandung City, Indonesia - Candra Utama; Nurwidiyanto Nurwidiyanto; Farhan Baehaki; Sri Ekawati (Universitas Lampung, 2021)
Salted fish is one of the processed fish products that are in great demand by the people of Indonesia. This type of preparation has good durability with natural processes. However, there are some cases that use chemicals as preservatives, such as formaldehyde. This study aims to determine the formaldehyde content in salted fish that is traded in the market in Indonesia. This research is descriptive and the sample is taken from Ciroyom Market, Bandung City, Indonesia, randomly. Samples were analyzed qualitatively to observe the physical characteristics of salted fish. In addition, quantitative analysis was also carried out to determine the level of formaldehyde present in salted fish using a UV-Vis spectrophotometer at a wavelength of 520 nm. The results of the analysis showed that 4 of the 15 samples tested contained formaldehyde with a concentration of 0.033 – 0.482 ppm. The characteristics of these samples physically also have similarities with the characteristics of fish containing formaldehyde, namely bright white and hard textured.